Silent echoes: understanding and predicting the widespread mental health impact of mass shootings - Aadi Mishra; Max E. Coleman (Frontiers in Public Health, 2026)
Half of the 20 deadliest US. mass shootings have occurred in the past decade. We propose and find that the mental health consequences of such shootings are not confined to the immediate community but affect Americans nationwide. We merge two datasets, the Household Pulse Survey and the Northeastern University Mass Killing Database to assess that nationwide effect. Our dataset links 20 consecutive Household Pulse waves (March 2022–November 2023; N ≈ 1,094,000 adults) with every public mass shooting in the same window (17 events). Using survey-weighted logistic regressions that incorporate replicate and person-level weights, we test whether the odds of screening positive for anxiety and depression are higher in survey waves following a public mass shooting compared with waves not preceded by a shooting. We find that mass shootings are associated with increased anxiety and depression after controlling for demographic and socioeconomic variables. Translating effect sizes to counts yields an estimated ~2.27 million additional adults screening positive for anxiety and ~1.29 million additional adults for depression nationwide after a public mass shooting. Moreover, our analyses indicate that higher death counts and younger victims are associated with increased nationwide effects. Analysis of data from survey waves immediately before and after the 2022 Robb Elementary School shooting finds that anxiety and depression increased and that the size of the effect was inversely proportional to geographic distance from the shooting. Therefore, our results indicate that the mental-health costs of mass shootings are widespread, and it is critical to offer public-health responses that extend beyond the immediate communities where mass shootings occur.